Parent Involvement in Pre-Kindergarten and the Effects on Student Achievement - Kimberly McDowell; Ashlie Jack; Meredith Compton (The Advocate, 2018)
An ever-present achievement gap has been found among students and their peers. Educational research and literature have found that the growing gap is due in part to a lack of parent involvement in their students’ education and academic performance. The purpose of this study was to investigate how parent involvement affects student achievement and academic success in Pre-Kindergarten. It was hypothesized that parents who display higher levels of involvement will have children who perform better academically. The participants in this study included 26 preschool children and their parents. The researcher utilized a curriculum-based measurement, AIMSweb, and IGDI’s (Indicators of Individual Growth and Development for Infants and Toddlers), a pre-k assessment measure used to monitor and assess early literacy development in preschool children. A modified version of the Parent Involvement Project Questionnaire (PIPQ) was also used to determine if there is a positive correlation between parent involvement and student achievement. Results of the study indicate that invitation from school was statistically correlated with role construction and parent self efficacy but that student achievement was not statistically correlated with any of the scales from the parental involvement survey. Because the results were based on self-report and included a relatively small sample size, the outcomes of the study may not align with the majority of published studies pertaining to parent involvement and student achievement, due to its subjective nature. Or, perhaps for some students, there may be other factors that are more influential than parent involvement. Implications and further research are discussed.